Induction motor behavior due to unsymmetrical and symmetrical faults - Surya, Hardi; Ismail, Daut, Prof. Dr.; Risnidar Chan Bahaudin; Muhammad Irwanto; Rosnazri, Ali; Indra, Nisja (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.